Extracellular vesicle–depleted fetal bovine and human sera have reduced capacity to support cell growth - Eitan, Erez (J Extracell Vesicles, 2015)
BACKGROUND: Fetal bovine serum (FBS) is the most widely used serum supplement for mammalian cell culture. It supports cell growth by providing nutrients, growth signals, and protection from stress. Attempts to develop serum-free media that support cell expansion to the same extent as serum-supplemented media have not yet succeeded, suggesting that FBS contains one or more as-yet-undefined growth factors. One potential vehicle for the delivery of growth factors from serum to cultured cells is extracellular vesicles (EVs). METHODS: EV-depleted FBS and human serum were generated by 120,000g centrifugation, and its cell growth–supporting activity was measured. Isolated EVs from FBS were quantified and characterized by nanoparticle tracking analysis, electron microscopy, and protein assay. EV internalization into cells was quantified using fluorescent plate reader analysis and microscopy. RESULTS: Most cell types cultured with EV-depleted FBS showed a reduced growth rate but not an increased sensitivity to the DNA-damaging agent etoposide and the endoplasmic reticulum stress–inducing chemical tunicamycin. Supplying cells with isolated FBS-derived EVs enhanced their growth. FBS-derived EVs were internalized by mouse and human cells wherein 65±26% of them interacted with the lysosomes. EV-depleted human serum also exhibited reduced cell growth–promoting activity. CONCLUSIONS: EVs play a role in the cell growth and survival-promoting effects of FBS and human serum. Thus, it is important to take the effect of EV depletion under consideration when planning EV extraction experiments and while attempting to develop serum-free media that support rapid cell expansion. In addition, these findings suggest roles for circulating EVs in supporting cell growth and survival in vivo.